Effect of fire severity and presence of bamboo (Chusquea culeou) on soil chemical properties in Andean Patagonian forests of Argentina - Urretavizcaya, María Florencia (2025)
Background. Fire is recurrent in Patagonian forests of Argentina, and is frequently associated withthe die-off of bamboo (Chusquea culeou). Fire induces changes in soil properties, which mayaffect vegetation recovery. Aims. This study assesses how fire severity affects soil chemicalproperties in different Patagonian forests, in the absence and presence of C. culeou. Methods.We collected samples from the upper 5 cm of mineral soil from 44 plots distributed in five foresttypes affected by low-severity and high-severity fire, and unburned areas. Half of the plots alsohad C. culeou. Key results. Fire severity affected soil pH, organic matter, electrical conductivity,nitrogen, C:N ratio, and cation exchange capacity. Changes in organic matter and C:N ratio variedamong forest type, and variations in pH and sodium were detected among forest types. Thepresence of C. culeou affected soil pH, C:N ratio, and calcium. Conclusions. The changes recorded were expected and could have a lasting effect on long-term productivity. Nothofagus pumilio and Nothofagus antarctica, and forests with C. culeou, varied in theirsoil chemical properties, sometimes regardless of fire. Implications. Considering the heterogeneity of vegetation and soil in postfire environments is vital for predicting possible successional trajectories and defining restoration objectives.